PENGARUH INOVASI PRODUK, KEPERCAYAAN MEREK, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN HONDA BEAT DI SURAKARTA - ERLINA TIKA ARYANI; HENY KURNIANINGSIH (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study intends to ascertain the effects of product innovation, brand trust, and product variety on Honda Beat motorcycle purchases in Surakarta. This study employed a quantitative methodology. The method of sampling that involves a questionnaire. The quantitative statistical analysis stage of data collection employs the usage of data instrument testing (validity and reliability tests), hypothesis testing and the conventional assumption test (normality test, multicollinearity test, and heteroscedasticity test) (linear regression test, t test, f test, and determination test). The study's sample consisted of 100 people. According to the study's findings, Honda Beat motorbike purchases in Surakarta are significantly and partially influenced by product innovation. 2) In Surakarta, brand trust has a small but considerable impact on Honda Beat motorcycle purchases. 3) Partially, product diversity has significant influence on purchasing decisions for Honda Beat motorbikes in Surakarta.